Queer kinship and comparative literature new approaches - Sathi, Anchit; Ferrebe, Alice 1970- (Palgrave Macmillan, 2024)
This edited collection provides a critical forum for scholars to examine the evolution of queer kinship—encompassing the wide range of relationships, both biological and nonbiological, that queer individuals choose (or are compelled) to establish—through its representation in literature over time and across cultural contexts. In particular, the ten essays in this collection utilize close readings, philosophy, and theory to address the following question: How can we conceptualize the nature of queer kinship based on its textual representations?To this end, the essays engage with a diverse array of texts, from Buddhist writing to contemporary song lyrics, French literature from the 17th and 18th centuries to contemporary drama and novels from Sweden, Israel, and the Anglosphere. This broad temporal and geographic scope yields new critical insights into the varied ontologies of queer kinship and highlights the inherent paradoxes and fundamental messiness in queer kinship formations across different times, spaces, and contexts. In doing so, the collection makes a significant and timely contribution to the fields of kinship studies, queer studies, and comparative literature
Keywords: Queer theory; Comparative literature; Queer-Theorie; Vergleichende Literaturwissenschaft